Recent progress in synergistic chemotherapy and phototherapy by targeted drug delivery systems for cancer treatment. (31st October 2018) - Cao, Jie; Chen, Zuxian; Chi, Jinnan; Sun, Yalin; Sun, Yong
Abstract: Although it's pharmacological effect for cancer therapy, conventional chemotherapy has been compromised by a series of shortcomings such as limited stability, nonspecific tumour targeting ability and severe toxic side effects. To overcome these limitations, multifunctional targeted drug delivery systems for combinatorial therapeutics have been widely explored as novel cancer therapy strategies, showing encouraging results in many pre-clinical animal experiments. Among them, synergistic phototherapy and chemotherapy have demonstrated their abilities to enhance therapeutic efficacies and reduce unwanted side effects via a variety of mechanisms. In this review, we will summarize the latest progress in the development of targeted drug delivery systems with combinations of phototherapy and chemotherapy and discuss the important roles of phototherapy agents involved in those non-conventional therapeutic strategies.